Spontaneous Fission Barriers Based on a Generalized Liquid Drop Model - 郭树青 包小军 李君清 张鸿飞 (Communications in theoretical physics, 2014)
The barrier against the spontaneous fission has been determined within the Generalized Liquid Drop Model （GLDM） including the mass and charge asymmetry, and the proximity energy. The shell correction of the spherical parent nucleus is calculated by using the Strutinsky method, and the empirical shape-dependent shell correction is 6mp10yed during the deformation process. A quasi-molecular shape sequence has been defined to describe the whole process from one-body shape to two-body shape system, and a two-touching-ellipsoid is adopted when the superdeformed one-body system reaches the rupture point. On these bases the spontaneous fission barriers are systematically studied for nuclei from 2a~Th to 249 Cm for different possible exiting channels with the different mass and charge asymmetries. The double, and triple bumps are found in the fission potential energy in this region, which roughly agree with the experimental results. It is found that at around Sn-like fragment the outer fission barriers are lower, while the partner of the Sn-like fragment is in the range near l~SRu where the ground-state mass is lowered by allowing axially symmetric shapes. The preferable fission channels are distinctly pronounced, which should be corresponding to the fragment mass distributions.